2005
DOI: 10.1002/app.21596
|View full text |Cite
|
Sign up to set email alerts
|

A study of localized curing of glass‐filled composites using microhardness measurements

Abstract: Extent of cure of hybrid composite systems is examined by conducting hardness measurements at different stages of the photopolymerization reaction and obtaining kinetic parameters that matched the experimental data. The materials are commercial dental composites based on bis[4-(2-hydroxy-3-methacryloyloxypropoxy)phenyl]propane resins with different photoinitiator concentrations as well as filler particle sizes and combinations. Samples (five per group) were made using nylon molds (2.5 ϫ 5 mm) of the tested com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Perhaps the filler composition of the materials reduced their translucency, and this led to lower energy density in the deeper layers. Moreover, it was reported that the coefficient factor ( k ) was much lower for the bottom surfaces compared with the top surfaces of the composite specimens. This reduction in the value of k was more severe for the material with a higher concentration of photoinitiator and a higher percentage of glass filler particles in the wavelength range affecting the photopolymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the filler composition of the materials reduced their translucency, and this led to lower energy density in the deeper layers. Moreover, it was reported that the coefficient factor ( k ) was much lower for the bottom surfaces compared with the top surfaces of the composite specimens. This reduction in the value of k was more severe for the material with a higher concentration of photoinitiator and a higher percentage of glass filler particles in the wavelength range affecting the photopolymerization.…”
Section: Discussionmentioning
confidence: 99%